2022
DOI: 10.1007/s12517-022-10475-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of precipitation and human activities on suspended sediment transport load in the Velika Morava River Basin (Serbia)

Abstract: Sediment transport time series have shown a severe change in the suspended sediment load transported by the Velika Morava River (Republic of Serbia) during the last few decades. The research objectives of this study were to determine the suspended sediment trends, and to assess the impact of variations in precipitation and human activities on the suspended sediment load. The causes and timing of this severe decrease were analyzed, and the results show that there has been a significant sudden shift downwards fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The second factor of land use changes is also high index of the population aging. Later, Manojlović et al (2021Manojlović et al ( , 2022 demonstrated similar results in research for the Južna Morava river basin (A = 15,469 km 2 , comprising the Nišava watreshed) and for the Velika Morava river basin encompassing the Južna Morava river basin (A = 37,561 km 2 ). In both studies, it is shown that the decrease of rural population and areas of agricultural and arable land were directly related to the decline of suspended sediment.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The second factor of land use changes is also high index of the population aging. Later, Manojlović et al (2021Manojlović et al ( , 2022 demonstrated similar results in research for the Južna Morava river basin (A = 15,469 km 2 , comprising the Nišava watreshed) and for the Velika Morava river basin encompassing the Južna Morava river basin (A = 37,561 km 2 ). In both studies, it is shown that the decrease of rural population and areas of agricultural and arable land were directly related to the decline of suspended sediment.…”
Section: Introductionsupporting
confidence: 64%
“…This research is an extension of the study of Manojlović et al 2022. The Figure 1 refers to the spatial presentation of depopulation/population growth and deagrarization/agrarization growth in the Velika Morava river basin (which is 42.5% of the territory of the Republic of Serbia) located in the Central Serbia.…”
Section: Study Area Datasets and Methodsmentioning
confidence: 99%
“…The second factor of land use changes is also high index of the population aging. Later, Manojlović et al [4,5] demonstrated similar results in research for the Južna Morava river basin (A = 15,469 km 2 , comprising the Nišava watreshed) and for the Velika Morava river basin encompassing the Južna Morava river basin (A = 37,561 km 2 ). In both studies, it is shown that the decrease of rural population and areas of agricultural and arable land were directly related to the decline of suspended sediment.…”
Section: Introductionmentioning
confidence: 55%
“…This research is an extension of the study of Manojlović et al [5]. The Figure 1 refers to the spatial presentation of depopulation/population growth and deagrarization/agrarization growth in the Velika Morava river basin (which is 42.5% of the territory of the Republic of Serbia) located in the Central Serbia.…”
Section: Study Area Datasets and Methodsmentioning
confidence: 95%